Implementing a divergent response? The UK approach to bribery in international and domestic contexts. Issue 5 (3rd July 2020) - Lord, Nicholas; Doig, Alan; Levi, Michael; van Wingerde, Karin; Benson, Katie
ABSTRACT: This paper analyses UK domestic bribery. The authors argue that in both domestic and international contexts, cases are not numerically significant but that changes in how the UK government approaches bribery in the international context means that, where once domestic bribery was addressed more rigorously than bribery in the international context, this imbalance may be being steadily reversed. The paper concludes by setting out the implications that this identifiable divergence may have for the effective policing of bribery in the domestic context. The paper makes an empirical and theoretical contribution to the literature on corruption in the UK. IMPACT: This paper analyses the UK response to bribery and corruption and provides evidence of a divergent approach, in terms of strategy, policy and enforcement action, to addressing bribery in the domestic and international contexts. This has adverse implications for the prevention, detection, and investigation of bribery. In order to reduce the divergence and reinforce the domestic focus, governments need to ensure better and more detailed data for monitoring of the extent of bribery, the presence of a single lead for the domestic context to ensure consistency and co-ordination, and the availability of training for relevant staff to make certain relevant stakeholders are alert to emerging corruption issues. The empirically informed insights and arguments in this paper are relevant to policy-makers and practitioners working in the area of anti-corruption, as well as non-governmental organizations seeking to scrutinize anti-corruption strategies, policies and practice in the UK.